Evaluasi Pelaksanaan Kuliah Kerja Lapangan dalam Mendukung Pelestarian Ekosistem Pesisir di Kampung Melayu, Kota Batam - Akhmad Farhan; Dian Nandista; Dini Selviana Putri; Stevani Batamah Putri; Tifany Rahmadanny; M Arpah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Coastal ecosystems provide important ecological, social, and economic benefits for communities living in coastal areas. However, coastal ecosystems face various pressures caused by environmental degradation, waste accumulation, human activities, and limited public awareness. Higher education institutions can contribute to coastal ecosystem conservation through field-based learning activities that involve students and local communities. This study aims to evaluate the implementation of the Field Work Lecture (Kuliah Kerja Lapangan/KKL) in supporting coastal ecosystem conservation in Kampung Melayu RW 08, Batam City. This study employed a descriptive qualitative approach supported by activity documentation and field observations. Data were collected through observation, documentation, informal interviews, and evaluation of the activities conducted during the KKL program. The evaluation focused on activity planning, implementation, community involvement, environmental education, and potential sustainability of the program. The results indicate that KKL activities provide opportunities for students to apply academic knowledge in real community settings while contributing to environmental awareness and coastal conservation efforts. Community involvement is an important factor in determining the effectiveness and sustainability of conservation activities. However, the implementation of short-term field activities requires follow-up programs, continuous monitoring, and stronger collaboration among universities, communities, and local stakeholders. Therefore, KKL should not only be viewed as an academic activity but also as a participatory learning and community engagement program that can contribute to sustainable coastal ecosystem conservation.